67 TECHNOLOGY TO SUPPORT INDEPENDENT LIVING AT HOME: ONLINE SURVEY OF USER NEEDS AND REQUIREMENTS. (25th October 2022) - Murphy, C; Timon, C; Heffernan, E; Hopper, L; Gallagher, P; Hussey, P
Abstract: Background: Technology can play a key role in supporting older adults to live independently at home. A User Needs and Requirements study including co-design workshops and an online survey was conducted to inform the development of a technological solution aimed at supporting older adults to remain living independently at home. The online survey component is reported here. Methods: Eligibility criteria included that respondents were older adults living at home or caregiving stakeholders providing care to older adults at home e.g. family caregivers or health/social care professionals. Recruitment took place throughout Ireland through civil society organisations and age friendly networks in local councils. Quantitative and qualitative data were gathered from June to July 2020. Descriptive statistics were applied to quantitative data and inductive thematic analysis was performed on free text responses. Results: In total, 380 respondents completed the survey (n= 235 older adults, n=77 family caregivers, n=47 healthcare professionals and n=21 home support workers). Older adults identified key issues where technology might support them to live independently, these included, home security (33% n=77), falls (30% n=69), reduced mobility (23% n=55) and loneliness (23% n=54). Thematic analysis highlighted key areas where technology could assist stakeholders in providing care for older adults living independently, these included, remote monitoring of family members (family caregivers), communication with clients (healthcare professionals) and falls (home support workers). Older adults reported that data privacy and the cost of technology were key concerns. All groups reported a high level of willingness to use technology such as ambient sensors, wearable devices and voice activated assistants to support independent living. Conclusion: Results of this survey provide insights into user needs and requirements in combination with results from co-design workshops to inform the design, development and trial of a technology system to support independent living at home.